SPREADING OF VIRUS HEPATITIS A DISEASE AMONG THE POPULATION AND MAIN FACTORS AFFECTING IT - K.Xabibullayeva Nargiza; Vakhabova Dilnoza; Mamadjanova E`zoza; Yuldasheva Rislig`oy; Rakhmanov Izzatilla (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. In fact, viral hepatitis is one of the serious health problems. Because 500 million people in the world are infected with hepatitis, and 80% of them do not have the opportunity to be examined and treated. Viral hepatitis A takes an important place among them. The fact that this disease is widespread among children, who are our future heirs, shows that it is necessary to deeply study not only the methods of treatment of this disease, but also the causes of its origin. This disease is observed not only in young people, but also among adults. The curves in the statistics of the disease show that the disease is not evenly distributed throughout the region, and this gives rise to the idea that the foci of the disease should be studied on a large scale. Viral hepatitis A disease is becoming an important socio-economic problem today. A lot of research is being conducted all over the world, including in Uzbekistan, to study viral hepatitis A. However, despite research, the rate of disease among children is increasing significantly.